THE MEDICINAL PROPERTIES OF THE DOCK PLANT BELONGING TO THE POLYGONACEAE FAMILY - Nilufar Dilshod qizi Sayfullayeva; Behzod Qodirov (Western European Studies, 2025)
Dock is a group of annual and perennial plants belonging to the Polygonaceae family. There are 16 species of dock in Uzbekistan. These include cultivated Dock, Curly Dock (R. crispus L.), Red Dock (R. conglomerates Murr.), Syrian Dock (R. syriacus Meisn.), and Drobov’s Dock (R. drobovii Korov.). The root is a taproot, thick, and the stem is multi-angular and segmented with a hairy upper part. The basal leaves are long-stalked, the leaf blades are triangular, lanceolate or broad-arrow-shaped, while the stem leaves are elongated-lanceolate and arranged alternately in segments. The flowers are unisexual, small, and form racemose inflorescences. It blooms from May to September and produces three-angled nut-like fruits. The plant grows in damp places, meadows, and mountain slopes. In medicine, the root of dock, as well as the curly and common docks, are used. Dock is rich in vitamins such as S, C, and others, and is used as food. Dock and sycamore leaves are large plants.
Keywords: Rumex; Polygonaceae family; curly dock